Project Implementation of Corporate Information Systems (ERP and MES) as a Guarantee for Increasing the Operational Efficiency of the Enterprise - Shevchenko, N.; Moiseienko, K.; Latysheva, O. (Економічний вісник Донбасу, 2022)
This article delves into the intricacies of implementing corporate information systems, such as Enterprise Resource Planning (ERP) and Manufacturing Execution System (MES). It has been established that the implementation of ERP and MES ensures increased operational efficiency of the enterprise by automating various processes. Additionally, the MES system controls multiple production stages, from raw material input to finished product shipment, thereby reducing errors and increasing task execution speed. ERP and MES also facilitate data and information consistency between different departments, providing all levels of management access to the same company information, streamlining the decision-making process. Furthermore, ERP allows for the collection of data on finance, personnel, logistics, and production in one system, making the planning and decision-making process simpler. The MES system can be used to determine task execution time and distribute it among workers based on their skills and abilities. Lastly, ERP and MES enable companies to prioritize tasks, control their execution, automate processes, improve task execution quality and speed, and ensure data and information consistency between different departments. The article discusses the importance of corporate information systems (CIS) in modern companies with a priority of maintaining a competitive position. The key components of such a system are enterprise resource planning (ERP) and manufacturing execution systems (MES), which ensure the integrity, accuracy, and speed of data exchange between all company units. Implementing ERP and MES is a guarantee of increasing the company's operational efficiency in complex production conditions. CIS help companies ensure data and information unity between different departments, enabling quick and efficient decision-making processes. У статті досліджено особливості проєктного впровадження корпоративних інформаційних систем, таких як ERP (Enterprise Resource Planning) та MES (Manufacturing execution system). Встановлено, що впровадження корпоративних інформаційних систем (ERP та MES) є гарантією підвищення операційної ефективності підприємства, оскільки дозволяє автоматизувати багато процесів на підприємстві. З’ясовано, що система MES дозволяє контролювати різні етапи виробництва, починаючи від входу сировини і закінчуючи відвантаженням готової продукції, що знижує кількість помилок та підвищує швидкість виконання завдань. Встановлено, що ERP та MES допомагають забезпечити єдність даних та інформації між різними департаментами, що дозволяє всім рівням управління мати доступ до однакової інформації про діяльність підприємства, тим самим роблячи процес прийняття рішень швидким та ефективним. Визначено, що ERP дозволяє збирати дані про фінанси, кадри, логістику та виробництво в одній системі, що спрощує процес планування та прийняття рішень. Сформульовано, що за допомогою системи MES можна визначити час, необхідний для виконання певного завдання та розподілити його між робітниками відповідно до їхніх навичок та здібностей. Доведено, що ERP та MES дозволяють підприємствам визначати пріоритетність завдань та контролювати їх виконання, допомагають підприємствам автоматизувати процеси, покращувати якість та швидкість виконання завдань, забезпечувати єдність даних та інформації між різними департаментами, та контролювати виконання завдань.